2016
DOI: 10.1038/nchem.2571
|View full text |Cite
|
Sign up to set email alerts
|

MIDA boronates are hydrolysed fast and slow by two different mechanisms

Abstract: MIDA boronates (N-methylimidodiacetic boronic acid esters) serve as an increasingly general platform for building-block-based small molecule construction, largely due to the dramatic and general rate differences with which they are hydrolysed under various basic conditions. Yet the mechanistic underpinnings of these rate differences have remained unclear, hindering efforts to address current limitations of this chemistry. Here we show that there are two distinct mechanisms for this hydrolysis: one is base-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 32 publications
7
99
0
1
Order By: Relevance
“…Deprotection can proceed through two different mechanisms: (1) under strong aqueous base, rate-limiting attack of hydroxide on the carbonyl carbon, or (2) under weakly basic or neutral aqueous conditions, slower rate-limiting attack of water on the boron-nitrogen bond. 137 This mechanistic divergence is consistent with extensive reaction kinetics, kinetic isotope effects, 18 O labelling, and computational data. In-situ slow release of MIDA boronates has been advantageous for many reactions including couplings of unstable heteroarylboronates, 138,139 polymerization reactions, 140141 asymmetric methodologies, 142 the synthesis of organic photovoltaics, 143 and a one-pot homologation of boronic acids.…”
Section: Advances Towards a General Platform For Iterative Small Molesupporting
confidence: 76%
“…Deprotection can proceed through two different mechanisms: (1) under strong aqueous base, rate-limiting attack of hydroxide on the carbonyl carbon, or (2) under weakly basic or neutral aqueous conditions, slower rate-limiting attack of water on the boron-nitrogen bond. 137 This mechanistic divergence is consistent with extensive reaction kinetics, kinetic isotope effects, 18 O labelling, and computational data. In-situ slow release of MIDA boronates has been advantageous for many reactions including couplings of unstable heteroarylboronates, 138,139 polymerization reactions, 140141 asymmetric methodologies, 142 the synthesis of organic photovoltaics, 143 and a one-pot homologation of boronic acids.…”
Section: Advances Towards a General Platform For Iterative Small Molesupporting
confidence: 76%
“…30,31 In the oxidative system this was not particularly problematic, since the rate of oxidation was rapid. However, this has clear implications for transition metal catalysis using organoboron species under basic biphasic reaction conditions ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These masked reagents are presumed to work by slowly revealing the corresponding boronic acid by hydrolysis under typical aqueous basic reaction conditions. Recent investigations by Lloyd-Jones et al have shown that in certain cases such as trifluoroboronate salts 12 as well as MIDA boronates 13 a hydrolysis step is required prior to the transmetalation event.…”
Section: Introductionmentioning
confidence: 99%